Lifestyle changes among older adults during and after COVID-19 pandemic in Lithuania - Skirmante Sauliune; Ramune Kalediene; Vytenis Kalibatas; Snieguole Kaseliene; Olga Mesceriakova (Frontiers in Public Health)
The aim of this studyto analyze lifestyle changes among older adults during and after COVID-19 pandemic in Lithuania, with a particular focus on eating habits, physical activity, social engagement and harmful habits.MethodsThe representative sample of Lithuanian population over 65 years old (1,503 individuals) was involved in the questionnaire survey, performed in January 2024.ResultsMost of the eating habits and the body weight of the older adults did not change during the COVID-19 pandemic in Lithuania. Respondents noted that their physical activity decreased, face-to-face communication became rarer, while remote communication increased. During pandemic, the increased frequency of snacking was more often indicated by persons with lower than secondary education, working, receiving higher incomes, as well as increased snacking and body weight were more prevalent among younger, single or overweight persons; increased body weight during the pandemic was more often mentioned by the persons who assessed their health poorly. Physical activity decreased more often among rural residents and groups with higher or college education; face-to-face communication has become rarer among younger people, rural residents, pensioners, disabled, people with higher income and those with overweight, while remote communication has increased among women, respondents with a university education and those with an average income (p < 0.05). Nearly half of the respondents indicated that the changes in food consumption and smoking frequency that occurred during the pandemic remained after it. After the pandemic, the habits of consuming fast food, confectionery or other sweets and changes in body weight mostly remained, while the patterns of communication returned to the pre-pandemic level. Most of the healthy lifestyle habits formed during the pandemic persisted after the pandemic. The lifestyle habits formed during the pandemic remained more stable in the groups of older persons, residents of smaller towns, respondents with lower than secondary education, higher income, singles, disabled, obese, and those who assessed their health poorly (p < 0.05).ConclusionDuring the COVID-19 pandemic in Lithuania, there were various changes in eating habits, physical activity, communication patterns, and harmful habits. Certain habits formed during the pandemic continued afterward, particularly among specific groups of the older Lithuanian adults.